Perceived effectiveness of messages to address cervical cancer screening barriers: An online experiment - Sarah M. Halvorson-Fried; Isabella C.A. Higgins; Melissa B. Gilkey; Allison J. Lazard; Marissa G. Hall (PLoS ONE, 2025)
Introduction Cervical cancer is almost entirely preventable through vaccination and screening, but screening rates still lag targets. Communication campaigns can encourage screening; however, the types of message content that are most effective are unknown. Methods We conducted an online randomized experiment testing messages within four themes aligned with previously identified screening barriers: cancer fatalism, inconvenience, lack of knowledge about risk factors, and unawareness of screening guidelines. A national convenience sample of US participants aged 21–65 years and assigned female at birth ( n = 1,536) viewed one of three messages from each theme assigned at random and one control message in random order. We measured perceived effectiveness to encourage cervical cancer screening, anticipated social interactions, and self-reported learning. Mixed-effects linear models examined the impact of message theme on each outcome on a scale from 1 (low) to 5 (high). Results All four barrier-focused themes encouraged cervical cancer screening more than the control (perceived message effectiveness mean and standard deviation: cancer fatalism = 3.44 (1.21); convenience = 3.43 (1.23); risk factors = 3.25 (1.23); screening guidelines = 3.44 (1.19); control message = 2.45 (1.35), p < .001). Barrier-focused messages similarly outperformed the control on anticipated social interactions and self-reported learning (all p < .001). Messages were less effective for participants who had never been screened or were out-of-date. However, regardless of screening status, barrier-focused messages outperformed the control. Conclusions Messages targeting known barriers to cervical cancer screening were perceived as more effective than a control message. These messages could increase cervical cancer screening rates if used in interventions at scale.